Creating the Child Audience: Media and the Invention of Modern American Childhood - Thibaut Clément (Transatlantica)
An introduction to the thematic dossier, this contribution situates the emergence of child-media in the larger history of the media in the United States. After raising the question of the place assumed by children, teenagers, and young adults in the media system that targets them, as well as the roles they get to play in it, this introduction presents the contributions in the dossier.